Diffusionseigenschaften von Nickel in einer Festoxid-Brennstoffzelle - Haremski, Patricia (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2022)
In this work, thermal grooving experiments were performed on anode microstructures, Ni polycrystals and Ni bicrystals. The grain boundary grooves were measured by means of an AFM. The results provide for the first time reliable values as well as the complete anisotropy of the relevant material parameters - the relative grain boundary energies and the surface diffusion coefficients - of nickel under realistic operating conditions of an SOFC anode.